CRITICAL VELOCITY VERIFICATION THROUGH FOUR VELOCITIES OF AMATEURS RUNNERS (Fiep Bulletin - online, 2013)
The search of new indexes capable to predict human performance is extremely interesting, once starting from these, it's possible to prescribe, in a more efficient way, a training program, besides favoring a more precise evaluation to the effects of the training. Objectives: To determine the time obtained in the distance of 500 meters, 1500 meters, 3000 meters e 5000 meters, and to verify through the relationship time/distance the possibility to find the critical velocity (Vcrit) between the four distances where the energetic systems utilization are distinct. Methods: Were selected to the study seventeen runners, who are experienced for running middle and long distances. The four distances were performed in a track of 200 meters with the aim to identify the critical velocity through the angular coefficient of the straight line of lineal regression between the respective times and distances: 1- 500 meters; 2- 1500 meters; 3- 3000 meters; 4- 5000 meters. Results: Were found a correlation between the distances 3 and 4. The critical velocity achieved it was of 20,02 ± 2,28 Km/h, 18,35 ± 2,14 Km/h, 16,46 ± 2,11 Km/h and 16,19 ± 1,99 Km/h, for the distances of 500 m, 1500 m, 3000 m e 5000 m, respectively. Conclusion: We can observe with this study that in field tests intended to determine the Vcrit we must take in consideration the energetic ways mobilization.
Keywords: Field Tests; Critical Velocity; Energetic Systems